2008
DOI: 10.1016/j.coal.2008.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Coalbed methane producibility from the Mannville coals in Alberta, Canada: A comparison of two areas

Abstract: The Mannville coals in the Fenn area, Alberta Plains, have desorbed gas content averaging 8.57 cm 3 /g (275 scf/t

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 14 publications
0
29
0
Order By: Relevance
“…The consequence of this uncertainty means that it is difficult to predict with accuracy a well's performance until it is online and producing (Acuna, et al, 2015;Gentzis, et al, 2008;Howell, et al, 2014;Karacan, 2013;Xie, et al, 2013). However, a pipe network to gather the gas needs to be in place before the wells begin producing, and as the performance of the wells are not accurately known until they are producing, this presents a design challenge.…”
Section: Unconventional Gas Reservoir Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation
“…The consequence of this uncertainty means that it is difficult to predict with accuracy a well's performance until it is online and producing (Acuna, et al, 2015;Gentzis, et al, 2008;Howell, et al, 2014;Karacan, 2013;Xie, et al, 2013). However, a pipe network to gather the gas needs to be in place before the wells begin producing, and as the performance of the wells are not accurately known until they are producing, this presents a design challenge.…”
Section: Unconventional Gas Reservoir Uncertaintymentioning
confidence: 99%
“…There are many physical factors that are related to coal permeability but are difficult to quantify (Gentzis, et al, 2008). Even in a laboratory setting, it is not easy to measure the relative permeability of coal mainly because of the difficulty in reproducing results (Ham & Kantzas, 2013).…”
Section: Unconventional Gas Reservoir Uncertaintymentioning
confidence: 99%
“…The micro-pilot test results showed that the gas saturation is 40.8% in the anthracitic coals of the South Qinshui basin, China [58]. Seam 4 in the Lower Cretaceous Gates Formation, Inner Foothills of Alberta showed gas saturation levels of 90% in the in situ reservoir conditions [53]. Unsaturated CBM reservoirs initially produce CBM only when the reservoir pressure is reduced below the critical desorption pressure [59,60].…”
Section: Recovery Mechanism Of Unsaturated Cbm Reservoirsmentioning
confidence: 99%
“…Thus, unsaturated CBM reservoirs refer to those reservoirs in which gas content is less than their maximum gas adsorption in the reservoir conditions. Most coal reservoirs can be substantially unsaturated with thermogenic gas [45][46][47][48][49][50][51][52][53][54][55][56][57][58]. Gas saturation of coal reservoirs in the Weibei CBM field ranges from 39.2%~87.2% [55,56].…”
Section: Recovery Mechanism Of Unsaturated Cbm Reservoirsmentioning
confidence: 99%
See 1 more Smart Citation